Comprehensive breast cancer study: About 6 cases - Sabini, Graciela; Musé, Ignacio; Viola Alles, Alberto; Torres, Miguel (Cirugía del Uruguay, 1986)
Stressed is the importance of correct diagnosis of breast tumors, in which the anamnesis and physical examination are of unquestionable value. Study of paraclinical techniques best defining the characteristics of said tumor: radiology, ultrasound, dynamic telethermographic study, citology and histopathological study as well as the determination of estrogen receptors. Presentation of six cases of breast cancer selected at the Mastology Unity and studied by means of the clinical description, the radiology, the telethermography and the estrogen receptors. In said cases the difierent techniques complemented each other to reach a correct diagnosis and/or to adopt therapeutic procedures by evaluation of the prognostic factors in each case.